Morphological analysis of ischemia-reperfusion injury in a cold ischemia model of jejunal free flap for hypopharyngeal reconstruction. Issue 1 (January 2020) - Mauramati, Simone; Morbini, Patrizia; Ferrario, Giuseppina; Alnemr, Mohamed; Luka, Elona; Occhini, Antonio; Bertino, Giulia; Klersy, Catherine; Alessiani, Mario; Benazzo, Marco
Abstract: Background: Jejunal free flap (JFF) reconstruction is a popular treatment option for advanced hypopharyngeal cancer. Several factors including ischemia-reperfusion injury (IRI) can cause mucosal damage and progressive flap necrosis. We investigated the development and time-related progression of morphological and cellular changes in patients with JFF reconstruction including cold preservation of the graft. Methods: Eleven patients were enrolled. Biopsies were taken during surgery from normally perfused tissue, before loop isolation (T0), at the end of back-table surgery (T1), immediately before reperfusion (T2), 15′ after reperfusion (T3), and at the end of the digestive anastomoses (T4) and from the external monitor daily from the 1st to the 5th postoperative day (M1–M5). Histomorphological and immunohistochemical parameters in the intraoperative and postoperative samples were evaluated and compared. Results: Delayed flap necrosis was observed in 2 patients. The cold ischemia phase did not negatively affect mucosal regeneration after reperfusion; morphological and cellular damage parameters returned to normal by the end of surgery or along the early postoperative period. Significant enterocyte replication activity was observed at the end of revascularization, which continued in the postoperative phase, leading to recovery of the epithelial morphological integrity and disappearance of apoptotic cells. An inflammatory infiltrate persisted in the M samples, and in a significant proportion of samples, mucosal fibrosis developed by the end of the postoperative observation. Conclusion: Cold perfusion and preservation of the JFF can effectively limit the negative effects of IRI and to prevent short- and medium-term complications that can compromise the final outcome.